2014
DOI: 10.2217/cpr.14.72
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive geriatric assessment in the older cancer patient: coming of age in clinical cancer care

Abstract: Cancer care at the extremes of life, in the young and the old, is characterized by unique issues associated with pediatrics and geriatric medicine, accentuated by the special vulnerabilities of these groups. In response to these needs, the field of pediatric oncology has been well honed to deal with the special problems associated with juvenile cancer patients. While most adult oncologists consider themselves well prepared to deal with older cancer patients, the current expansion of the geriatric population – … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 127 publications
(130 reference statements)
1
32
0
1
Order By: Relevance
“…Less adequate management is offered to patients with STS over 90, in particular regarding pretreatment imaging and surgery. Of note, oncogeriatric assessment is not part of the NETSARC data set, and it is likely that coexisting conditions have largely contributed to these differences with younger patients. However, when patients over 90 are treated with surgery according to clinical practice guidelines (within NETSARC, the ESMO guidelines are used as reference), relapse‐free survival and PFS remain similar to that of the younger population in univariate and also multivariate analysis where classical prognostic factors are introduced .…”
Section: Discussionmentioning
confidence: 99%
“…Less adequate management is offered to patients with STS over 90, in particular regarding pretreatment imaging and surgery. Of note, oncogeriatric assessment is not part of the NETSARC data set, and it is likely that coexisting conditions have largely contributed to these differences with younger patients. However, when patients over 90 are treated with surgery according to clinical practice guidelines (within NETSARC, the ESMO guidelines are used as reference), relapse‐free survival and PFS remain similar to that of the younger population in univariate and also multivariate analysis where classical prognostic factors are introduced .…”
Section: Discussionmentioning
confidence: 99%
“…[4,[11][12][13] The CGA found to be useful in determining prognosis, risks, and treatment benefits and laying the groundwork for interventions to improve patient outcomes. [4,14] Previous studies showed that individualized care developed through CGA was helpful in achieving maximum treatment efficacy and minimum toxicity; whereas non-CGA based care of older adults diagnosed with cancer resulted in disruptions. [15,16] Deschodt et al [17] (2013) reported that the multidisciplinary CGA approach has three stages: 1) case finding or screening (identifying high-risk groups), 2) assessment (comprehensive assessment), and 3) implementation (evidence-based care based on need).…”
Section: Data Collection Toolsmentioning
confidence: 99%
“…These aspects analyse the morbidity and mortality of cancer and highlight health problems that might interfere with cancer treatment. Geriatric assessments should thus be included in clinical trials to improve quality of life during cancer treatment and survival [6,35,36]. Furthermore, health economists should also consider patients' health status along with age.…”
Section: Comprehensive Geriatric Assessmentmentioning
confidence: 99%
“…Furthermore, health economists should also consider patients' health status along with age. Chemotherapy might not be cost-effective for all elderly patients but can be (cost-) effective for the fitter elderly [36]. Thus, the functional health of geriatric patients should be considered in health economic evaluations to reach a more precise assessment of cost-effectiveness that do not generalise such a heterogeneous patient group.…”
Section: Comprehensive Geriatric Assessmentmentioning
confidence: 99%